A Revenue Analysis on Taiwan’s Publishing Industries from the Prospective of Knowledge Discovery Using Government’s Financial Database - Ming-Ju Hsu (Jiàoyù zīliào yǔ túshūguǎn xué, 2017)
This research focused on retrieving and analyzing data and information from the “Financial Database” established by the Ministry of Finance of Republic of China (Taiwan), carrying out a Knowledge Discovery from the Financial Database (KDFD) 2013~2015, primarily on Taiwan’s Nine(9)-subclass Publishing Industries. The results of the research showed that: a). the sales revenues of Taiwan’s Publishing Industries have declined year after year from 2013 to 2015; b). within the year there was a wave of steep drop in sales from May to June, then the sales revenues gradually recovered and reached the peak in November to December and c). Newspapers, magazines and books publishing were still the dominate part of the sales for the Publishing Industries (82.1%). While the Digital Publishing Industries accounted for an average of 16% of total sales revenues from 2013 to 2015, the growth spurs from 11% in 2013 to 16% in 2014, then to 20% in 2015 were quite impressive, indicating a potential growth for Digital Publishing Industries. The definition of the publishing industries categorized by the government of Taiwan included nine subclasses in the whole division, further study could be conducted for each subclass of the publishing division to obtain its actual sales revenues for a more realistic comparison with surveyed data.